Pendampingan UMKM dalam Meningkatkan Volume Penjualan dan Inovasi di Era Digital Pada UMKM Warung Mama Ifit - Pristiya, Nika; Nurkarantina, Nurkarantina; Meliyansyah, Putri; Wahyuni, Putri; Ramlah, Ramlah; Mentari, Theresia (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community mentoring activity aims to provide mentoring to Warung Mama Ifit in an effort to increase sales volume and product innovation through the application of digital technology. The mentoring method uses the Participatory Action Research (PAR) Approach. The mentoring program, which was implemented from August 7 to September 30, 2024, includes the preparation, implementation and evaluation stages. The results of the study showed a significant increase in the development of business identity, systematic financial recording, and expansion of market reach through consistent online promotions. The conclusion of this mentoring is that a strong business identity, mature business planning, systematic financial management, and effective marketing strategies can position Warung Mama Ifit to achieve greater success in the future and has the potential to become a model for other MSMEs to increase their competitiveness in the digital era